Rapid green synthesis and characterization of silver nanoparticles arbitrated by curcumin in an alkaline medium - Khan, Muhammad Jamshed; Shameli, Kamyar; Sazili, Awis Qurni; Selamat, Jinap; Ramiah, Suriya Kumari (MDPI, 2019)
Green synthesis of silver nanoparticles is desirable practice. It is not only the required technique for industrial and biomedical purposes but also a promising research area. The aim of this study was to synthesize green curcumin silver nanoparticles (C-Ag NPs). The synthesis of C-Ag NPs was achieved by reduction of the silver nitrate (AgNO3) in an alkaline medium. The characterizations of the prepared samples were conducted by ultraviolet visible (UV-vis) spectroscopy, powder X-ray diffraction (PXRD), field emission scanning electron microscopy (FESEM), high-resolution transmission electron microscopy (HRTEM), selected area electron diffraction (SAED) and zeta potential (ZP) analyses. The formation of C-Ag NPs was evaluated by the dark color of the colloidal solutions and UV-vis spectra, with 445 nm as the maximum. The size of the crystalline nanoparticles, recorded as 12.6 ± 3.8nm, was confirmed by HRTEM, while the face-centered cubic (fcc) crystallographic structure was confirmed by PXRD and SAED. It is assumed that green synthesized curcumin silver nanoparticles (C-Ag NPs) can be efficiently utilized as a strong antimicrobial substance for food and meat preservation due to their homogeneous nature and small size.